A STUDY OF OLIVER TWIST INFERIORITY ON CHARLES DICKENS’S OLIVER TWIST - Hikmaharyanti, Putu Desi Anggerina; Jayantini, I Gusti Agung Sri Rwa; Utami, Ni Made Verayanti (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2021)
This study focuses on Oliver Twist inferiority feeling during his childhood life. Oliver Twist as the main character of the novel experienced several miserable treatments from people around him. Along with the inferiority feeling, unfortunately it brings some effects towards him. This is the reason of why this study created by describing the inferiority feelings together with the impact qualitatively. Since the study is in literature matter, psychological and sociological approaches were applied to elaborate the inferior feeling experienced by the main character. There were five settings where Oliver Twist got bad treatment done by several supporting figures and made him become an innocent, rebel and courageous boy as the effects of those inferiority in this study.